Islam dan Barat oleh Sayyid Abu Al-Hasan ’Ali Al-Nadwi - Saari, Che Zarrina (Jurnal Usuluddin, 2000)
This article is divided into two parts, the first of which reviews the thought of Sayyid Abu al-Hasan ’Ali al-Nadwi on the relationship between Muslim and the Western Civilazations. The second part is the Malay version of his "Islam and the West".